Bee Movie - Denton, Andrew; Gibbons, Andrew (Brill, 2023)
Bee Movie is a short film that invites questions for conversations on visual ethics. The viewer is invited into a world of circular, tragic and absurd questions concerning what a filmmaker, an abstract writer, a journal editor, and a film viewer ought to do when observing the apparent reality of a bee’s circular attempts to escape a pond. As a filmmaker and abstract writer, one does not want to tell the viewer and reader how one feels about this bee, bees, insects, ponds, water, life, death and circles. And one feels obliged not to explain the context through which the film came to life as the bee was engaged in efforts that might be narrated as lifesaving but also as another complex of efforts entirely. As an open image, without our textual dissection (or, at least, with a dampening of that dissection to an abstract and with a few questions and challenges), we regard Bee Movie as inviting questions about the ethics of the use of images as pedagogy. Whatever we thought about whether and how to share this film, we find ourselves in 359 other relationships, and always back again to what we assumed might be the starting position.
Keywords: Ethics; Pedagogy; Absurdity; 3901 Curriculum and pedagogy